2016
DOI: 10.1016/j.applthermaleng.2016.03.098
|View full text |Cite
|
Sign up to set email alerts
|

Phase change behavior of latent heat storage media based on calcium chloride hexahydrate composites containing strontium chloride hexahydrate and oxidation expandable graphite

Abstract: Calcium chloride hexahydrate(CaCl 2 •6H 2 O) composites PCMs containing strontium chloride hexahydrate (SrCl 2 •6H 2 O) and oxidation expandable graphite(EGO) were prepared and phase change behavior of CaCl 2 •6H 2 O/EGO/SrCl 2 •6H 2 O composite PCMs, including supercooling degree, phase change temperature, latent heat, density, thermal conductivity and thermal stability were systematically studied. Results demonstrate that thermal conductivity, heat transfer and the latent capacities of the CaCl 2 •6H 2 O/SrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…However, its supercooling degree is up to 20 • C. Sutjahja [24] used SrCl 2 ·6H 2 O (1.0 wt %), Ba 2 CO 3 (0.5 wt %), and K 2 CO 3 (0.5 wt %) as additives to CaCl 2 ·6H 2 O. It was found that SrCl 2 ·6H 2 O exerted the best effect on CaCl 2 ·6H 2 O, this result was consistence with paper [25]. Palittin [26] adopted sonocrystallization method which used ultrasound radiation for promoting CaCl 2 ·6H 2 O to crystallize and results indicated this technique made crystals have uniform distribution and dense arrangement.…”
Section: Supercooling Of Salt Hydratessupporting
confidence: 55%
“…However, its supercooling degree is up to 20 • C. Sutjahja [24] used SrCl 2 ·6H 2 O (1.0 wt %), Ba 2 CO 3 (0.5 wt %), and K 2 CO 3 (0.5 wt %) as additives to CaCl 2 ·6H 2 O. It was found that SrCl 2 ·6H 2 O exerted the best effect on CaCl 2 ·6H 2 O, this result was consistence with paper [25]. Palittin [26] adopted sonocrystallization method which used ultrasound radiation for promoting CaCl 2 ·6H 2 O to crystallize and results indicated this technique made crystals have uniform distribution and dense arrangement.…”
Section: Supercooling Of Salt Hydratessupporting
confidence: 55%
“…It can be inferred that CaCl 2 ·2H 2 O, as an effective nucleation agent, can reduce the substantial supercooling of the PCM system, while nano SiO 2 particles have a positive effect in reducing supercooling. With the synergistic action of the two materials, the performances and properties of the newly developed PCM system can be better—especially in terms of supercooling—than reported in previous research [ 7 , 14 , 22 , 23 ]. We would like to mention here that no segregation occurred for all of the PCMs that were used in this research.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, some researchers [7,8,9] found that adding graphene (0.02 wt %) could reduce the supercooling degree of pure water. On other studies, Li et al [10,11] confirmed that SrCl 2 ·6H 2 O could reduce the supercooling of inorganic PCM. Therefore, it has been suggested that the usage of graphene oxide (GO) can be greatly reduced with the presence of SrCl 2 ·6H 2 O to have the effect on supercooling reduction.…”
Section: Introductionmentioning
confidence: 97%